Metabolic syndrome in human immunodeficiency virus-infected patients. (October 2018) - Duro, M; Manso, MC; Barreira, S; Rebelo, I; Medeiros, R; Almeida, C
The objective of this study was to investigate the factors underlying the development of metabolic syndrome (MetS) in HIV-infected patients. Two hundred and sixty-six clinical cases were selected for a retrospective study. The sample was classified using the Adult Treatment Panel III guidelines and the identification of risk or protective factors associated with MetS evaluated via multivariate logistic or multinomial regressions. HIV-infected individuals diagnosed with MetS tend to be older, overweight, or obese (85% have a BMI ≥ 25), with a waist circumference > 90 cm (96.5 [88.8–105.5] cm, median [interquartile range]). Blood testing these individuals revealed high fasting levels of insulin (8.1 [5.8–21.6] pg/ml), glucose (98.0 [84.0–116.0] mg/dl), triglycerides (201.0 [142.0–267.3] mg/dl), and high-density lipoprotein cholesterol (36.5 [29.8–43.3] mg/dl) in addition with higher levels of inflammatory mediators such as high-sensitivity C-reactive protein (2.5 [1.0–4.9] mg/dl) and interleukin-6 (3.4 [2.8–3.8] pg/ml). The likelihood of HIV-infected individuals who are virally suppressed developing MetS is about 60% higher than those with acute infection. Treatment with nucleoside reverse transcriptase inhibitors (NRTIs) and protease inhibitors (PIs) increases the chance of developing MetS by around 2.4 times. Individuals with a lower antioxidant capacity (total antioxidant status [TAS] <1.33) have a 2.6 times higher risk of developing MetS. HIV-related chronic inflammation, a low TAS, and treatment with NRTIs in association with PIs are additional MetS risk factors.